Prognostic importance of lymphovascular invasion in urothelial carcinoma of the renal pelvis. Issue 12 (6th April 2018) - Danzig, Matthew R.; Mallin, Katherine; McKiernan, James M.; Stadler, Walter M.; Sridhar, Srikala S.; Morgan, Todd M.; Bochner, Bernard H.; Lee, Cheryl T.
Abstract : BACKGROUND: The current study was conducted to assess the impact of lymphovascular invasion on the survival of patients with urothelial carcinoma of the renal pelvis. METHODS: Patients with urothelial carcinoma of the renal pelvis who underwent radical nephroureterectomy from 2010 through 2015 were identified in the National Cancer Data Base. Patients were characterized according to demographic and clinical factors, including pathologic tumor stage and lymphovascular invasion. Associations with overall survival were assessed through proportional hazards regression analysis. RESULTS: A total of 4177 patients were identified; 1576 had lymphovascular invasion. Patients with T3 disease and lymphovascular invasion had 5‐year survival that was significantly worse than that of patients with T3 disease without lymphovascular invasion (34.7% vs 52.6; P  < .001 by the log‐rank test), and approached that of patients with T4 disease without lymphovascular invasion (34.7% vs 26.5%; P  = .002). On multivariate analysis controlling for age, comorbidities, grade, lymph node status, surgical margin status, race, sex, and chemotherapy administration, patients with T3 disease and lymphovascular invasion also were found to have significantly worse survival compared with patients with T3 disease without lymphovascular invasion (hazard ratio, 1.7; 95% confidence interval, 1.4‐1.91). CONCLUSIONS: Lymphovascular invasion status is a key prognostic marker that can stratify the risk of patients with pT3 upper tract urothelial carcinoma further. Patients with this pathologic feature should be carefully considered for clinical trials exploring existing and novel therapies. Cancer 2018;124:2507‐14. © 2018 American Cancer Society . Abstract : Patients with pathologic T3 cancer of the renal pelvis and lymphovascular invasion have significantly worse survival compared with patients with pathologic T3 disease without lymphovascular invasion, approaching the survival of patients with pathologic T4 disease. Lymphovascular invasion can aid in the risk stratification of patients with upper tract urothelial carcinoma.